Patient’s willingness to pay for improved community health insurance in Tanzania - Kassimu Tani; Brianna Osetinsky; Sally Mtenga; Günther Fink; Fabrizio Tediosi (Health Policy Open, 2024)
Globally, achieving universal health coverage remains significant challenge. Health insurance coverage in low- and middle-income countries is still low with only a few African countries managed to reach 50% coverage. This study aimed to investigate the factors influencing patients’ willingness to pay (WTP) for medication and various versions of the improved Community Health Insurance Fund (iCHF) in Tanzania. A facility-based cross-sectional study was conducted in all hospitals, health centres, and eight randomly sampled dispensaries, sampling participant from the queue, one out of every three patient based on their order of entry into consultation room, and interviewed 1,748 patients in Kilombero and Same districts in Tanzania. We used multi-stage Contingent Valuation Methods exploring data collected during client exit interviews. We employed a random utility model and estimated WTP through an ordered logit model. The independent variables were; patient’s gender, age, marital status, education, employment status, Non-Communicable Disease (NCD) status, health insurance status, and the type of healthcare facility level. Our findings revealed that most patients exhibited a WTP of an amount equivalent to the current iCHF premiums and would also be willing to pay for an augmented iCHF premium inclusive of additional medication coverage. Upon adjusting for demographic characteristics, we observed that patients enrolled in an insurance program or benefiting from user fee waivers demonstrated a lower WTP for medication, while those with non-communicable diseases (NCDs) and seeking care in private facilities exhibited a higher WTP. Furthermore, patients with a secondary education level or above generally displayed higher WTP for premiums. Conversely, patients enrolled in private insurance and availing user fee waivers, along with those accessing care in public facilities, demonstrated a lowered WTP for iCHF premiums. These results highlight the need for targeted interventions to address systemic deficiencies and improve access to medicines. Our conclusions is that policies considering NCD status, education levels and income status are important when designing health insurance schemes for the informal sector in Tanzania, with the goal of increasing uptake of CHF.